The implementation of Informatics subject in the Kurikulum Merdeka at SMP 26 Bandung - Rina Tri Agustianis (Hipkin Journal of Educational Research, 2025)
This study aims to describe the implementation of the Informatics subject within the Merdeka Curriculum at SMP 26 Bandung. A qualitative descriptive method was employed, with data collected through in-depth interviews, classroom observations, and literature review. The findings indicate that although the implementation has been initiated, it still faces several challenges such as the lack of teachers with an Informatics background, inadequate facilities, and suboptimal teaching and assessment methods. The Informatics subject primarily focuses on developing basic skills, particularly in using Microsoft Office, and does not group students based on their ability levels. Nevertheless, this approach has encouraged peer collaboration and fostered a supportive learning environment. To enhance learning effectiveness, ongoing professional development for teachers, especially those from non-informatics disciplines, is essential. The study also highlights the potential of cross-disciplinary learning to enrich digital literacy. Overall, the research emphasizes the need for strengthening teacher capacity, institutional support, and adequate learning infrastructure as strategic efforts to ensure the delivery of relevant, inclusive, and adaptive Informatics education in response to the evolving demands of the digital era.   Abstrak Penelitian ini bertujuan untuk mendeskripsikan implementasi mata pelajaran Informatika dalam Kurikulum Merdeka di SMP 26 Bandung. Metode yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan studi kepustakaan. Hasil penelitian menunjukkan bahwa implementasi pembelajaran Informatika telah berjalan meskipun menghadapi sejumlah kendala, seperti keterbatasan guru yang memiliki latar belakang dalam bidang Informatika, sarana prasarana yang belum memadai, serta belum optimalnya metode pembelajaran dan evaluasi yang diterapkan. Mata pelajaran Informatika di sekolah ini difokuskan pada penguasaan keterampilan dasar penggunaan Microsoft Office, tanpa mengelompokkan peserta didik berdasarkan tingkat kemampuan. Namun, pendekatan ini justru mendorong kolaborasi antar peserta didik dan menciptakan lingkungan belajar yang suportif. Untuk mendukung efektivitas pembelajaran, diperlukan pelatihan berkelanjutan bagi guru serta pengembangan pembelajaran lintas mata pelajaran. Penelitian ini menekankan pentingnya penguatan kapasitas pendidik, dukungan kebijakan sekolah, dan penyediaan fasilitas sebagai upaya strategis dalam menghadirkan pendidikan Informatika yang relevan dan adaptif terhadap perkembangan zaman serta kebutuhan peserta didik di era digital. Kata Kunci: kurikulum pendidikan; Kurikulum Merdeka; mata pelajaran Informatika